1995
DOI: 10.1111/j.1475-2743.1995.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus transformations as affected by crop residue management practices and their influence on crop yield

Abstract: A 15-year field experiment investigated crop residue management practices, with crop residue removal, burning and incorporation as the main treatments and nitrogen levels as subtreatments. The effects of crop residue management practices on rice and wheat yield were measured for 11 years. Surface soil samples were taken to study nitrogen and phosphorus immobilization/adsorption and their release under laboratory conditions. The field experiment indicated that residue burning and residue removal resulted in gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 9 publications
2
52
1
Order By: Relevance
“…Other studies have shown that straw retention has no significant effect on the available P in soil (Malhi et al 2011;Prasad et al 1999;Yadvinder et al 2008). Beri et al (1995) observed a decrease in the available P content in soil after 11 consecutive years of straw retention in an Indian ricewheat rotation cropping area. In the same area, Bhandari et al (2002) reported that the available P in soil decreased significantly after 10 consecutive years of straw retention after the rice season.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Other studies have shown that straw retention has no significant effect on the available P in soil (Malhi et al 2011;Prasad et al 1999;Yadvinder et al 2008). Beri et al (1995) observed a decrease in the available P content in soil after 11 consecutive years of straw retention in an Indian ricewheat rotation cropping area. In the same area, Bhandari et al (2002) reported that the available P in soil decreased significantly after 10 consecutive years of straw retention after the rice season.…”
Section: Introductionmentioning
confidence: 71%
“…Beri et al (1995) also claimed that when straw with high ratios of C:P was mixed with soil, the straw enhanced P adsorption in the soil within the same growth season (McGill and Cole 1981;Murrmann and Peech 1969;Medley et al 1982). Microbial activity has been shown to play a major role in redistributing P into different forms in the soil, and straw retention has been shown to affect the balance of P in the soil (McGill and Cole 1981;Murrmann and Peech 1969).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, it involves additional cost of labour, irrigation and extra tillage [4]. Moreover, observations of long term experiments indicate that though incorporation of agro-residues in soil improves soil health significantly [5][6][7], it decreases the subsequent crop yields due to production of microbial phytotoxins and allelochemicals [8] and immobilization of the available nitrogen [9]. Incorporation of agro-residues like paddy straw increases the CH 4 emission from field [10,11] especially in irrigated soils, which in turn adds to the malice of global warming.…”
Section: Introductionmentioning
confidence: 99%